Ecological justice in Indonesia and China post-mining land use? - Saputra, Rian; Zaid, M; Gunawan, Matthew Marcellinno; Pei-Chi , Wu (CV. Ius et Ambientis, 2024)
This paper thoroughly examines the regulation and implementation of post-mining land use in Indonesia and China. This study employs a statutory and comparative legal approach to examine both countries’ regulations and utilization of post-mining land. The research findings indicate that Indonesia lacks legal rules for post-mining land utilization. The Mineral and Coal Mining Law in Indonesia and other legislation solely governs the transfer of post-mining land from companies to eligible parties via the Minister, Governor, or Regent/Mayor. These provisions indicate that post-mining land use in Indonesia continues to adopt an anthropocentric perspective and has not yet embraced ecological justice. In China, the utilization of post-mining land is modified to align with ecological, social, and economic requirements, designating it for agricultural purposes, straw cultivation, and infrastructure, including agricultural land, straw fields, grasslands, forests, wildlife habitats, biofuel crops, and areas designated for industrial, commercial, and residential development. Interestingly, when the decision is made to convert post-mining state land into agricultural land, following feasibility approval by local authorities in China, the transfer is granted to rural communities collectively or to those surrounding the post-mining area for management as agricultural land.